Systematic evaluation of peer‐to‐peer systems using PeerfactSim.KOM. (22nd December 2015) - Feldotto, Matthias; Graffi, Kalman
Summary: Comparative evaluations of peer‐to‐peer protocols through simulations are a viable approach to judge the performance and costs of the individual protocols in large‐scale networks. In order to support this work, we present the peer‐to‐peer system simulator PeerfactSim.KOM, which we extended over the last years. PeerfactSim.KOM comes with an extensive layer model to support various facets and protocols of peer‐to‐peer networking. In this article, we describe PeerfactSim.KOM and show how it can be used for detailed measurements of large‐scale peer‐to‐peer networks. We enhanced PeerfactSim.KOM with a fine‐grained analyzer concept, with exhaustive automated measurements and gnuplot generators as well as a coordination control to evaluate sets of experiment setups in parallel. Thus, by configuring all experiments and protocols only once and starting the simulator, all desired measurements are performed, analyzed, evaluated, and combined, resulting in a holistic environment for the comparative evaluation of peer‐to‐peer systems. An immediate comparison of different configurations and overlays under different aspects is possible directly after the execution without any manual post‐processing. Copyright © 2015 John Wiley & Sons, Ltd.